2017
DOI: 10.1590/0001-3765201720160805
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the Green Ground Snake Erythrolamprus poecilogyrus sublineatus (Serpentes: Dipsadidae) in Subtropical Brazil

Abstract: We investigated reproductive features of the dipsadid snake Erythrolamprus poecilogyrus sublineatus in the southernmost Brazilian coast, a subtropical region characterized by well-marked seasons. Females are significantly smaller than males, have a shorter tail, and reach sexual maturity at later times along their development. In contrast to tropical subspecies, E. p. sublineatus females presented a seasonal pattern, with secondary follicles occurring from late winter to early autumn and egg production restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 26 publications
8
10
0
1
Order By: Relevance
“…In both studied Philodryas species, females attained greater body sizes than males, which agrees with observations of P. patagoniensis from northern Argentina and southern Brazil (lópez andgiraudo 2008, loebens et al 2017) and other xenodontines (see Aguiar and Di-Bernardo 2005, Ávila et al 2006, Zanella and Cechin 2010, Prieto et al 2012, Mesquita et al 2013, Panzera and Maneyro 2013, Quintela et al 2017. Males of both Philodryas species presented significantly higher Tl/SVl ratios than females, but due to the overlapped range observed between sexes within both species, the character can not be considered absolutely dimorphic.…”
Section: Sexual Dimorphism and Reproductionsupporting
confidence: 87%
See 1 more Smart Citation
“…In both studied Philodryas species, females attained greater body sizes than males, which agrees with observations of P. patagoniensis from northern Argentina and southern Brazil (lópez andgiraudo 2008, loebens et al 2017) and other xenodontines (see Aguiar and Di-Bernardo 2005, Ávila et al 2006, Zanella and Cechin 2010, Prieto et al 2012, Mesquita et al 2013, Panzera and Maneyro 2013, Quintela et al 2017. Males of both Philodryas species presented significantly higher Tl/SVl ratios than females, but due to the overlapped range observed between sexes within both species, the character can not be considered absolutely dimorphic.…”
Section: Sexual Dimorphism and Reproductionsupporting
confidence: 87%
“…To determine the presence of sexual dimorphism, for each species we examined differences in SVL and in ratio Tl/SVl between males and females with a t test (Quintela et al 2017). For both species, the Sexual Size Dimorphism (SSD) index was calculated according to gibbons and lovich (1990), where SSD = mean SVl of the larger sex divided by the mean SVl of the smaller sex.…”
Section: Sexual Dimorphism and Reproductionmentioning
confidence: 99%
“…Females of Lygophis flavifrenatus attain greater total length than males, as well as the majority of dipsadids investigated so far (e.g. Aguiar & Di-Bernardo, 2005;Balestrin & Di-Bernardo, 2005;López & Giraudo, 2008, Pizzatto et al, 2008Zanella & Cechin, 2010;Mesquita et al, 2013;Panzera & Maneyro, 2013;Quintela et al, 2017). Body size in females is associated with fecundity so that a larger body can accommodate a larger offspring (Shine, 1994).…”
Section: Resultsmentioning
confidence: 98%
“…Among the several aspects of natural history, data on the reproductive biology are especially essential, considering its importance for the adoption of strategies for the species conservation (Shine & Bonnet, 2009;Almeida-Santos et al, 2014). Once scarce, studies on the reproductive aspects of Neotropical snakes have received a substantial increment in the past decades (Almeida-Santos et al, 2014), which included relevant investigations on species or populations occurring in subtropical climatic domains (Hartmann et al, 2004;Aguiar & Di-Bernardo, 2005;Balestrin & Di-Bernardo, 2005;Leite et al, 2009;Zanella & Cechin, 2010;Oliveira et al, 2011;Mesquita et al, 2013;Panzera & Maneyro, 2013;Rebelato et al, 2016;Loebens et al, 2017;Quintela et al, 2017). These studies revealed a predominant pattern of seasonal female reproductive cycle (restricted to the warmer period of the year) and marked sexual dimorphism, where females attain larger body sizes and males have tails comparatively larger.…”
mentioning
confidence: 99%
“…Fêmeas de serpentes da família Dipsadidae tendem a serem maiores que seus respectivos machos (López e Giraudo, 2008;Quintela et al, 2017), sendo esta uma característica morfológica associada à fecundidade e acomodação de seus ovos (Shine, 1994). No entanto, apesar de mais compridos, serpentes arborícolas tendem a apresentar corpo mais estreito, cauda alongada e certa compressão lateral (Vitt e Vangilder, 1983;Lillywhite e Henderson, 1993).…”
unclassified